Seasonality in fuel consumption: A case study of a gas station - Jo\~ao Rosado; Daniel Guerra; Paulo Ferreira (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
Oil and its derivatives are very important goods in the world, not only because of their huge use but also because the consequences of that use. The literature has plenty of works with economic analysis of the use of oil. Having available a huge amount of data, we propose an innovative approach: based on daily information of sales in a gas station since 2001 to 2018, we make a seasonality analysis of those sales. In separate analysis, using information of the both existing shifts, of the week day and of the month, we conclude that seasonality in sales is significant. This is an important information for firm managers, which could use this information to better define their strategies.
Keywords: C10; M10; M21; 330; diesel; fuel; gasoline; seasonality